(untitled) (Jurnal Arsitektur ARCADE, 2026)
The development of vertical housing in urban areas drives the need for environments that are not only spatially efficient, but also safe and livable. The concept of defensible space is an important approach in designing residential environments that can increase the sense of security by strengthening social and spatial control. This study aims to analyze the application of the principle of defensible space in vertical housing with an architectural psychology approach at the Springlake Apartment, Summarecon Bekasi. The method used is a qualitative case study through observation of physical elements and analysis based on four main principles, namely territoriality, natural surveillance, image and milieu, and access control. The results show that the application of these four principles contributes to increasing the perception of security and comfort of residents, although there are still several aspects that can be optimized, especially in strengthening access control and spatial legibility. This study contributes to the development of vertical housing design concepts that are oriented towards the psychological aspects of users and are relevant in the context of housing and real estate development in urban areas.